(untitled) (Journal of Intellectual Property and Information Technology Law (JIPIT), 2024)
Traditional communities possess creative expressions that tell their story and embody traditional knowledge. These creative expressions also form the basis for businesses which are as unique as the cultural heritage preserved from past generations. Hence, these expressions serve as a means of livelihood for members of the communities involved in the creativity. In addition, the cultural products maintain specific standards and represent the image of the communities, thus necessitating their protection through different aspects of intellectual property law. However, rights in Àdìrẹ, a traditional Yoruba hand-dyed textile characterized by intricate patterns and cultural significance, have been infringed by the production of their counterfeits for commercial reasons, to the detriment of the community originally producing and marketing them. Using Àdìrẹ textiles as a case study, this paper argues that the laws protecting the ingenuity in heritage products need to be set in motion to ensure the moral and economic interests of the communities while not undermining the interests of the public. As a qualitative research, this paper involves a doctrinal method that adopts analysis of both primary and secondary sources of the law and finds that Àdìrẹ textile is a tangible expression within the copyright framework that is of great cultural and economic benefit and deserving of adequate protection. It also finds that other intellectual property laws, such as trademark and/or ‘geographical indication’ are integral to preserving the integrity and cultural standard of Àdìrẹ. The authors recommend, among others, that the Copyright Commission investigates and redresses the infringement of the cultural intellectual property right in Àdìrẹ as an expression of folklore as enshrined in 78 of the Copyright Act.